1997
DOI: 10.1136/adc.77.5.431
|View full text |Cite
|
Sign up to set email alerts
|

An unusually severe phenotype for familial adenomatous polyposis

Abstract: Familial adenomatous polyposis (FAP) is a dominantly inherited predisposition to the development of many hundreds to thousands of adenomatous polyps of the colon. The mean age of onset is around 15 years, symptoms may arise in the third decade, and the median age for the development of colonic cancer is 35-40 years. Prophylactic colectomy reduces the risk of death from colorectal cancer to such an extent that late sequelae such as upper gastrointestinal tumours have become the main cause of mortality in approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 24 publications
1
28
0
1
Order By: Relevance
“…20 It was been reported that mutations located in the 5Ј one-half of exon 15 seem to lead to a more severe phenotype. 22,23 Some features such as appearance of adenomas at early ages (younger than aged 40 years), and aggressive metastatic carcinoma seen in our family were in agreement to those findings. Case 15 of this family was very interesting.…”
Section: Discussionsupporting
confidence: 90%
“…20 It was been reported that mutations located in the 5Ј one-half of exon 15 seem to lead to a more severe phenotype. 22,23 Some features such as appearance of adenomas at early ages (younger than aged 40 years), and aggressive metastatic carcinoma seen in our family were in agreement to those findings. Case 15 of this family was very interesting.…”
Section: Discussionsupporting
confidence: 90%
“…However, like our cases, there are also young children who present with a primary adenocarcinoma of the colon. Besides the early onset cases described here, Eccles and coworkers [3] reported a family where the index case was diagnosed with FAP at 7 years of age and with colon cancer at 9 years of age. Children with colorectal cancer usually have a far more advanced stage of disease at the time of recognition when compared to the general population.…”
Section: Discussionmentioning
confidence: 86%
“…In each family, DNA from an affected individual should always be tested in the first instance to identify the causative mutation [7]. If there is no living affected individual in a family from whom DNA can be obtained, it may still be feasible to carry out mutation detection if formalin-fixed paraffin blocks of tissue removed at the time of surgery are available from which DNA can be extracted [11].…”
Section: Methods Of Mutation Detectionmentioning
confidence: 99%
“…For example, a particularly severe phenotype has been seen in two families with mutations in exon 11. In these families, affected individuals were diagnosed as young as 5 years of age and cancer was detected in 1 individual aged 9 [7]. The presence of extracolonic manifestations can be used, however, to indicate where to look initially for mutations [30].…”
Section: Familial Adenomatous Polyposismentioning
confidence: 99%
See 1 more Smart Citation